2014
DOI: 10.1097/pas.0b013e3182a0218f
|View full text |Cite
|
Sign up to set email alerts
|

Gata3

Abstract: GATA3 is a transcription factor important in the differentiation of breast epithelia, urothelia, and subsets of T-lymphocytes. It has been suggested useful in the evaluation of mammary or urothelial origin or metastatic carcinomas, but its distribution in normal and neoplastic tissues is incompletely mapped. In this study, we examined normal developing and adult tissues in 2040 epithelial and 460 mesenchymal or neuroectodermal neoplasms for GATA3 expression to explore its diagnostic value in surgical pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(112 citation statements)
references
References 29 publications
7
103
2
Order By: Relevance
“…Granular cell tumors are relatively common benign neoplasms composed of large, eosinophilic cells with abundant coarsely granular cytoplasm, which most often involve the superficial soft tissues but also frequently occur in the mucosa of the gastrointestinal tract (11). Granular cell tumors are thought to show schwannian differentiation, and typically express S100 protein and SOX10 (11,12). Malignant granular cell tumors are exceedingly rare, and characterized by spindle cell morphology, prominent nucleoli, increased mitotic activity, geographic necrosis, marked pleomorphism, and increased nuclear to cytoplasmic ratio (11,13).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Granular cell tumors are relatively common benign neoplasms composed of large, eosinophilic cells with abundant coarsely granular cytoplasm, which most often involve the superficial soft tissues but also frequently occur in the mucosa of the gastrointestinal tract (11). Granular cell tumors are thought to show schwannian differentiation, and typically express S100 protein and SOX10 (11,12). Malignant granular cell tumors are exceedingly rare, and characterized by spindle cell morphology, prominent nucleoli, increased mitotic activity, geographic necrosis, marked pleomorphism, and increased nuclear to cytoplasmic ratio (11,13).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is also a diagnostically useful immunohistochemical marker which is sensitive and relatively specific for bladder and breast non-neoplastic tissues and carcinomas. In urothelial carcinomas, expression has been observed in 67%-86% of cases 24 , and 48%-94% of breast carcinomas have been positive with a decrease noted with higher grade tumors. 2, 4, 58 However, expression has also been occasionally observed in a variety of other tumors, including cutaneous squamous cell carcinoma, basal cell carcinoma, malignant mesothelioma, benign Brenner tumor, paraganglioma, pancreatic adenocarcinoma, and various types of salivary gland tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In urothelial carcinomas, expression has been observed in 67%-86% of cases 24 , and 48%-94% of breast carcinomas have been positive with a decrease noted with higher grade tumors. 2, 4, 58 However, expression has also been occasionally observed in a variety of other tumors, including cutaneous squamous cell carcinoma, basal cell carcinoma, malignant mesothelioma, benign Brenner tumor, paraganglioma, pancreatic adenocarcinoma, and various types of salivary gland tumors. 1,4,9 Although a number of series evaluating this marker in a spectrum of different tumors have not assessed expression in non-neoplastic trophoblastic tissues and trophoblastic neoplasms, 12 one recent large study by Miettinen et al included a small number of trophoblastic tissues/tumors and demonstrated that they frequently express GATA-3 (with positivity noted in trophoblastic cells of a developing embryo, pure choriocarcinomas, choriocarcinomatous components of mixed germ cell tumors, a placental site trophoblastic tumor, and syncytiotrophoblastic cells in seminomas).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because breast and sweat gland tissues have common embryologic origins and functions, so-called breast markers like GATA3, GCDFP and mammaglobin are also frequently expressed in sweat gland tumors [34,35,36]. However, the vast majority of low-grade invasive and in situ ductal carcinomas are positive for ER and PR, which are only rarely positive in skin adnexal lesions [37].…”
Section: Discussionmentioning
confidence: 99%